A sulfate polysaccharide/TNF‐related apoptosis‐inducing ligand (TRAIL) complex for the long‐term delivery of TRAIL in poly(lactic‐co‐glycolic acid) (PLGA) microspheres. (19th July 2012) - Kim, Hyemin; Jeong, Dooyong; Kang, Hee Eun; Lee, Kang Choon; Na, Kun
Abstract Objectives The aim was to develop a long‐term delivery system for Apo2 ligand/tumour necrosis factor‐related apoptosis‐inducing ligand (TRAIL) without chemical modification (such as pegylation). Methods A nanocomplex system between the positively charged TRAIL and the negatively charged chondroitin sulfate (CS) (CS/TRAIL) was designed and applied in poly(lactide‐co‐glycolide) (PLGA) microspheres (MSs). Key findings A nanocomplex of approximately 200 nm was easily formed in a weight ratio of 2 TRAIL to CS (TC2) at pH 5.0. The cytotoxicity of CS/TRAIL against HeLa cells was similar to that of native TRAIL. The complex also had higher loading efficiency (above 95%) in PLGA MSs prepared by the multi‐emulsion method than that of native TRAIL. The release behaviour of TRAIL from the PLGA MSs was monitored. Although the release of TRAIL from native TRAIL‐loaded PLGA MSs (TMS0) was almost complete after 3 days, TC2‐loaded PLGA MSs (TMS2) showed sustained TRAIL release without an initial burst for 10 days. The released TRAIL from TMS2 led to cytotoxicity accompanied by massive apoptosis of cancer cells. TMS2 significantly inhibited tumour growth in an in‐vivo xenograft model in mice, without any loss of body weight after treatment. Conclusions From the results, we concluded that TC‐loaded PLGA MSs have the potential for long‐term delivery of TRAIL without side effects.